Curious George: Librarian for a Day - Tibbott, Julie (Boston : Houghton Mifflin Harcourt, 2012)
Curious George helps out in the library and learns that organizing books makes them easier to find.
At head of title: Curious George.
"Curious George and related characters, created by Margret and H.A. Rey"--T.p. verso.
"Level 1, curious about organization"--Cover.
1
Keywords: Monkeys -- Fiction; Libraries -- Fiction; Orderliness -- Fiction; Early readers